2019
DOI: 10.1080/09638288.2019.1571116
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic injury survivors’ perceptions of their future: a longitudinal qualitative study

Abstract: Aim: Persistent disability following traumatic injuries can disrupt future plans and create uncertainty about how to mitigate future impacts. It is unknown how or whether perceptions of the future change in the years after injury. Therefore, the aim of this study was to explore trauma survivors' perceptions of their future over time. Methods: A longitudinal qualitative study, nested within a population-based longitudinal cohort study, was undertaken in Victoria, Australia with survivors of serious injury. Sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…Through semistructured interviews, both studies highlighted the complexity of establishing a definition of recovery, not least because perceptions of recovery change over time [13]. Findings also demonstrate how multiple factors such as pain, disability and return to work are impacted by anxiety and uncertainty following injury [14]. The themes of pain and disability are echoed in previous qualitative studies specifically focused to open lower limb fractures [15][16][17].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Through semistructured interviews, both studies highlighted the complexity of establishing a definition of recovery, not least because perceptions of recovery change over time [13]. Findings also demonstrate how multiple factors such as pain, disability and return to work are impacted by anxiety and uncertainty following injury [14]. The themes of pain and disability are echoed in previous qualitative studies specifically focused to open lower limb fractures [15][16][17].…”
Section: Introductionmentioning
confidence: 84%
“…Although the musculoskeletal trauma population has heterogeneity e.g. type of injury, severity, location and structure injured, it is anticipated based on previous research that similar findings across different subgroups will be common with smaller differences depending on type and injury severity [13][14][15][16][17]. Therefore, the higher sample size in this study will allow for the heterogeneity of the musculoskeletal trauma population and ensuring the breadth of this population is represented, as well as taking into account potential drop outs, acknowledging that loss to follow up is common in this population [24].…”
Section: Patient Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their systematic review, [37] reported that a wide range of evaluative studies found improved coping skills, reassurance and a sense of normalcy, reduction in isolation, information sharing, a better understanding of the experience and future, and in some cases, greater confidence in talking to physicians as a result of peer support amongst those burdened with illness. Work by [15] also reported that peer support can also can provide social support, promote resilience and coping strategies, and sharing of ideas while [38] reported that they can also help to cultivate adjustment and enhanced self-efficacy and adjustment following injury which can lead to improved outcome. In a review on peer support, [39] reported that, compared with professional intervention, peer support appears to more successfully promote hope and belief in the possibility of recovery; empowerment and increased self-esteem, self-efficacy and self-management of difficulties; and social inclusion, engagement and increased social networks.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to identify factors independently associated with late claim closure in older (65+ years) and younger (17‐64 years) adults following non‐catastrophic road traffic crash injury (RTI). Identifying older people at increased risk of late claim closure provides opportunities for early intervention of modifiable factors, such as pain catastrophising and postinjury comorbidities, and early implementation of support and coping strategies 19 …”
Section: Introductionmentioning
confidence: 99%